Iowa RBA, March 17, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for March 17, 1997. Highlights of the update include the continued presence of a Pinyon Jay and two Ross' Geese as well as sightings of a Red-shouldered Hawk, a Sandhill Crane, three Trumpeter Swans, and an estimated ten thousand Lapland Longspurs. Also included are handwritten notes for the next week's update with sightings of 14 species of Ducks and an Iceland Gull. Epson - sheet feed/flatbed